As Funções Hiperbólicas e suas Aplicações - Freitas, Maria do Bom Conselho da Silva Beserra (2015)
In this work we present a study about the Hyperbolic functions and their applications. We start with analysis of how these functions are approached in some di erential calculus books commonly used in graduate courses in exact sciences, noting that are made through its exponential setting. Then we exposed an approach using hyperbole as generating curve from the study of hyperbolic angles. The de nitions given it in parallel with the construction of the circular trigonometric functions, analyzing their similarities and di erences. Finally we present some of its applications, in particular and in more detail the catenary shape.